Eksistensi Manusia Dalam Pendidikan Serta Analisis Kebutuhan Akan Pendidikan - safira, putri silviana; amalia, sovi; islamiyah, binti rohmiatul; mustafsiroh, vifva khotul (Maliki Interdisciplinary Journal, 2024)
The existence of education is a crucial aspect of human development, as it contributes to the overall well-being of humans. Education encompasses various aspects of human life, including physical, intellectual, emotional, social, and spiritual aspects. It is essential for a well-rounded and effective education system. In Indonesia, the primary goal of education is to improve the intellectual capacity of the nation and provide quality education. The government has implemented various programs to support education, but there are still challenges and tensions. Comprehensive analysis of educational needs is crucial for effective implementation. The concept of education is not limited to traditional settings, as it encompasses various learning experiences. The government has implemented various programs to improve education quality, but there are still challenges and tensions. Pendidikan also plays a significant role in addressing the socio-economic status of the nation. The development of education is a continuous process that requires continuous improvement and adaptation to the changing needs of the society.